Kualitas Pelayanan Publik Dalam Pembuatan Kartu Kuning Di Dinas Tenaga Kerja Dan Transmigrasi Kabupaten Sukabumi - Sasmita, Bambang Primatama; Aryani, Lina (Peneliti.net, 2023)
Public service by the government is one manifestation of the function of the state apparatus as a servant of the community as well as a servant of the state, but one of the problems that often arises in relation between the government and the community is in the field of public service itself, especially in terms of quality. or the quality of government apparatus services to the community. The government as a service provider for the community is required to provide the best service. The aim of the study was to find out how the quality of service is in making a yellow card (AK-1) at the Sukabumi Regency Manpower and Transmigration Service and to find out the obstacles in the Yellow Card Making Service (AK-1) at the Sukabumi Regency Manpower and Transmigration Service. The method used in this study is using descriptive qualitative research, using data collection techniques through in-depth interviews, documentation and observation. This study uses the theory of service quality with the main informants in this study, namely the Head of the Sukabumi Regency Manpower and Transmigration Service, as well as supporting informants, namely the service apparatus and the people of Sukabumi Regency.